(untitled) (Research, Society and Development, 2022)
Objective: to present the profile of quality of life and symptoms of anxiety, depression and stress in university students in the healthcare area. Method: a descriptive study with a quantitative approach to data, carried out with university students in the healthcare field of three Federal Institutions of Higher Education in Minas Gerais. Variables such as sociodemographic, lifestyle, presence of depression symptoms, anxiety and stress, and quality of life (QoL) were measured. The QoL was assessed using the WHOQUOL-bref scale and symptoms of depression, anxiety and stress using the DASS-21 scale. A descriptive data analysis was performed. Results: 321 students participated in the study, mostly female (71.0%). More than 50% of the students had symptoms of depression, anxiety and stress, regardless of the level of severity, while severe/very severe symptoms were present in more than 20% of them, presenting a higher proportion in the nursing course. The psychological domain had the lowest overall QoL score (58.33), and the best was observed in the social relationships domain (66.67). Nursing students had the lowest scores while physical education students had the best scores in most domains. Medical students had the best score in the environment domain (68.75). Conclusion: Suggest the planning of policies and strategies that promote the physical and mental well-being of students, as well as screening and monitoring of most vulnerable ones, as well as those with mental health problems; such strategies can positively impact QoL.